Adaptive Environmental Management 2009
DOI: 10.1007/978-1-4020-9632-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Using Adaptive Management to Meet Multiple Goals for Flows Along the Mitta Mitta River in South-Eastern Australia

Abstract: In this chapter we reflect on a relatively small but influential example of adaptive management which seeks to enhance the environmental benefits of the flow regime in the highly regulated Mitta Mitta River in Australia's MurrayDarling Basin. In 1999 an operational review recommended the reintroduction of greater in-stream flow variability in the Mitta Mitta River in an attempt to improve river health. The river managers have worked towards this through managed variable releases from Dartmouth Dam. These varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Consistent with previous documented studies of social learning in environmental water management (e.g., Allan & Watts, 2018; Allan, Watts, Commens, & Ryder, 2009; Watts et al, 2010; Webb et al, 2018), the LTIM Adaptive Management Forum identified several key factors that are necessary to support exchange of learning and adaptive environmental water management: Trusted relationships between scientists, managers, land holders and other community members are critical to enabling adaptive management. Understanding the role of relationship building and consideration of this aspect in resourcing (time, effort, funding) is essential. Clear documentation, interpretation and communication of the processes to deliver environmental watering actions and outcomes are important and would improve transferability.…”
Section: Lessons Learnedsupporting
confidence: 90%
“…Consistent with previous documented studies of social learning in environmental water management (e.g., Allan & Watts, 2018; Allan, Watts, Commens, & Ryder, 2009; Watts et al, 2010; Webb et al, 2018), the LTIM Adaptive Management Forum identified several key factors that are necessary to support exchange of learning and adaptive environmental water management: Trusted relationships between scientists, managers, land holders and other community members are critical to enabling adaptive management. Understanding the role of relationship building and consideration of this aspect in resourcing (time, effort, funding) is essential. Clear documentation, interpretation and communication of the processes to deliver environmental watering actions and outcomes are important and would improve transferability.…”
Section: Lessons Learnedsupporting
confidence: 90%
“…For example, water transfers could begin earlier in the irrigation season or be released with a more natural hydrograph instead of constant flows. This approach was trialed for the transfer of water from Dartmouth to Hume reservoirs in the Murray-Darling Basin (Allan et al 2009;. Such changes can improve in-stream ecological condition and simultaneously achieve some social and economic objectives.…”
Section: Linking Operations Of Damsmentioning
confidence: 99%
“…Decisions need to be based on scientific evidence, including: assessments of the key flow components to be restored downstream of a dam; potential water losses or savings; synergies among floodplain management; reservoir flood control; hydropower production and water supply; and knowledge of risks and tradeoffs. Good communication and stakeholder support for dam reoperation can enable the process to proceed smoothly, building trust among individuals, organisations, society and governments (Allan et al 2009). Institutional structures are critical to support adaptive management.…”
Section: Constraints and Opportunities For Dam Reoperationmentioning
confidence: 99%
“…Therefore, dam reoperation and storage management requires great data, coordinated effort and finance. Judgements should be founded on systematic proof, including: evaluations of the key components of flow to be re-established downstream of a dam; possible water savings or losses; cooperative energies among floodplain management; dam flood control and knowledge of risks and trade-offs (Allan et al 2009).…”
Section: Dams and Considerations That Must Be Taken Through Their Desmentioning
confidence: 99%